To what extent can social enterprises contribute to sustainable development in the extractive industry in Madagascar? - VOOS, ROMIARY (2017)
This paper contributes to closing a knowledge/empirical gap on social enterprises’ realities and potential towards sustainable development in the extractive industry (EI) in Madagascar by linking stakeholders’ engagement in the industry with the necessary legal framework and emphasizing the key role potentially taken by social enterprises. The brief empirical analysis of comparable countries like South Africa, Kenya, Ghana and other sub Saharan African countries confirmed the importance of a minimal State’ engagement supported by private sector efforts for successful social enterprises implementation. Indeed, academic researches and case studies showed that in the context of resource-rich African countries, the lack of relevant regulatory framework led by a strong Government’ will to consider the EI as an engine of inclusive growth, might uncontrollably shift towards curse’ threaten including corruption, conflict and nation impoverishment. Political stability and commitment are seen as the main success’ factor and must go along with political continuity as the management of extractive industries extends on decades and demands long term sustainability management. On the other hand, this State’ strong and continuous involvement needs to proceed with the involvement of other relevant stakeholders. A key one is the private sector, including the EI operators who are frequently MNCs, with sustainability and corporate responsibility embedded in their strategic background. In countries where EI expertise starts from scratch, MNCs bear the responsibility to lead strategic initiatives involving multi-stakeholders’ platform when the Government is weak and unwilling to give the priority to collective interests. Precisely, in those cases, social business stand as a bridge allowing private initiatives to support and accompany the development of EI towards inclusive and durable growth while involving economic local actors and resources. Social enterprises are either individual entrepreneurs with small start-up capital who are less likely to fund it from the formal sector or SMEs to be integrated in the purchase cycle of the extractive industry, both schemes pointing to a possible room for policy interventions as their development requires State’ support. But both become a lever for sustainable development in the extractive industry if they are included in the supply chain and purchase cycle or through local content programmes. Further, business training, capacity building programmes and infrastructures construction need to be positively associated with quality performance and stabilization, while considering the specific context of Madagascar. This comes in addition to deploying training programs for women entrepreneurs, whose design and targeting should be revisited as Madagascar remains a matriarchal society where women can lead and implement positive and sustainable changes in economic, social and environment spheres. Government’ commitment and continuous leadership is therefore the only access to such ambitious transformative path. Thus, this paper will attempt to respond to the following precise question: to what extent can social enterprises contribute to sustainable development in the extractive industry (EI) in Madagascar?